COMPARATIVE STUDY ON CHARGED AND NEUTRAL PION-NUCLEON COUPLING CONSTANTS USING YUKAWA POTENTIAL MODEL (FUDMA JOURNAL OF SCIENCES, 2022)
The meson field theory based on the Yukawa model for nuclear forces is estimated using a simple relationship between the charged and neutral pion- nucleon coupling constant. This signifies that the charged coupling constant is larger compared to the value obtains for neutral pions. Therefore since np interaction is stronger than the pp interaction, we look at the value obtained for charged pion – nucleon constant which gives good agreement with one of the recent experimental values, and then the splitting between the charged and neutral pion – nucleon coupling constants is practically the same as that between charged and neutral pion mass. In this case, the mass difference between the charged and neutral pion is also calculated to assess the amount of charge dependence of the Neutron – Neutron scattering length
Keywords: Nucleaar forces, pp interaction, splitting, pion-nucleon